Minding the machine : languages of class in early industrial America - Rice, Stephen P. (Stephen Patrick), 1963- (University of California Press, 2004)
"In this book, Stephen P. Rice offers a new understanding of class formation in American during the several decades before the Civil War. This was the period in the nation's early industrial development when travel by steamboat became commonplace, when the railroad altered concepts of space and time, and when Americans experienced the beginnings of factory production." "Minding the Machine shows how members of a new middle class laid claim to their social authority and minimized the potential for class conflict by playing out class relations on less contested social and technical terrains. As they did so, they defined relations between shopowners - and the oversees, foremen, or managers they employed - and wage workers as analogous to relations between head and hand, between mind and body, and between human and machine." "Rice presents discussions of the mechanics' institute movement, the manual labor school movement, popular physiology reformers, and efforts to solve the seemingly intractable problem of steam boiler explosions. His narrative demonstrates that class is an much about the comprehension of social relations as it is about the making of social relations, and that class formation needs to be understood not only as a social struggle but as a conceptual struggle."--Jacket